2006
DOI: 10.1097/01.mib.0000217334.30689.3e
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of apoptosis during homeostasis and disease in the intestinal epithelium

Abstract: A single epithelial layer serves as the interface between the organism and the contents of the gastrointestinal tract, underlining the importance of regulating cellular viability despite an onslaught of pathogens, toxins, waste by-products, and cytokines. A balance between cellular proliferation and apoptosis is necessary to maintain this critical barrier. Recent findings have begun to explain the mechanisms by which intestinal epithelial cells are able to survive in such an environment and how loss of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
2
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 157 publications
(260 reference statements)
5
125
2
4
Order By: Relevance
“…Apoptosis results in the deletion of epithelial cells from the intestinal mucosa with an accompanying inflammatory response [12,13]. Cells undergoing apoptosis are ingested by phagocytic cells or shed into the intestinal lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis results in the deletion of epithelial cells from the intestinal mucosa with an accompanying inflammatory response [12,13]. Cells undergoing apoptosis are ingested by phagocytic cells or shed into the intestinal lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of IBD remains unclear, a number of studies have suggested a role of abnormal apoptosis in the intestinal epithelial cells (IECs), resulting from increased cytokine production, such as TNF, IL, and interferon family members (2). Increased IEC apoptosis has been detected at the acute inflammatory sites in UC (3,4) and CD patients (5).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the rate of intestinal epithelial cell apoptosis is central to the maintenance of an intact intestinal barrier. 64 The rate of intestinal epithelial cell apoptosis is increased in IBD leading to a loss of intestinal barrier function with subsequent exposure of the mucosal immune system to the microbiota. 65 Initial studies into the protective effects of pharmacologic hydroxylase inhibition revealed an antiapoptotic role for the pan-hydroxylase inhibitor DMOG in DSS colitis.…”
Section: Protective Mechanisms Of Hydroxylase Inhibitors In Ibd Inhibmentioning
confidence: 99%